PENGGUNAAN MEDIA PEMBELAJARAN FLASH CARD UNTUK MENINGKATKAN KOSA KATA BAHASA INGGRIS ANAK USIA DINI KELOMPOK B1 DI TK HANG TUAH - 3 SURABAYA - Harjunawati Harjunawati (Universitas Narotama, 2023)
This study aims to improve children's English vocabulary skills by using Flash Card media. This research was conducted on B1 level students of Hang Pour 3 Kindergarten Surabaya in the 2022/2023 academic year.This study used classroom action research which consisted of two cycles, namely cycle one and cycle two. The data collected was in the form of observation data on teacher activities, observation data on student activities, observation data on learning activities using flash cards. Based on the results of classroom action research in the first cycle and the second cycle, it was shown that learning using Flash Cards was able to increase abilities from developing to highly developed by 73%. Key words: Class action, Flash Cards, English Vocabulary